Characterizing interdisciplinarity in drug research: A translational science perspective. Issue 4 (November 2021) - Li, Xin; Tang, Xuli
Highlights: Few studies have managed to deeply examine the patterns and the roles of the interdisciplinarity in drug research. A novel bibliometric perspective, i.e., the translational science perspective, is used for analyzing interdisciplinarity in drug research. Four bibliometric indicators are proposed for characterizing interdisciplinarity of drug research. The results show that research within cell/molecular discipline needs more persistence to shorten the translational lags in drug research. Abstract: Background: Despite the significant advances in life science, it still takes decades to translate a basic drug discovery into a cure for human disease. To accelerate the process from "bench-to-bedside", interdisciplinary research (especially research involving both basic research and clinical research) has been strongly recommend by many previous studies. However, the patterns and the roles of the interdisciplinary characteristics in drug research have not been deeply examined in extant studies. Objective: The purpose of this study was to characterize interdisciplinarity in drug research from the perspective of translational science, and to examine the role of different kinds of interdisciplinary characteristics in translational research for drugs. Methods: In this paper, we analyze the interdisciplinary of drug research from a novel bibliometric perspective, i.e., a translational science perspective. 18 FDA approved drugs belonging to 6 categories are used as the research proxies. We propose four bibliometric indicators (i.e., Diversity of Research, Symmetry of Research, Persistence of Research and Stability of Research) for characterizing interdisciplinarity in drug research at both the macro and micro levels. We also design a bibliometric indicator (i.e., Translation Intensity) for quantifying the result of a drug's translation. Correlation analysis was also used to examine the relationships between these interdisciplinary characteristics of drug research and the translation intensity of drugs. Results: Multidisciplinary research (especially the research involving both basic and clinical disciplines) is still rare for all the 18 drugs and they generally occurred later than intra-disciplinary research in the timelines of drug research. The four interdisciplinary characteristics of drug research and the translation intensity of drugs both vary according to drugs. At the macro level, the diversity and symmetry of research have evident positive relationships with the translation intensity of drugs. At the micro level, the persistence of all seven kinds of research positively correlated with the translation intensity of drugs; and the persistence of multidisciplinary research have stronger relationships with the translation intensity of drugs than those of intra-disciplinary research except for the research within the cell/molecular discipline (CC research), which showed the most impressive correlations with the translation intensity of drugs. In addition, the stability of all kinds of research did not show a significant influence on the translation intensity of drugs. Conclusions: Interdisciplinary research engaging both basic science and clinical science should be encouraged in translational research for drugs. The basic research within the cell/molecular discipline needs more persistence to shorten the translational lags in drug research. Moreover, the methodology in this paper showcases a feasible way to characterize interdisciplinarity of research and measure the results of translation in drug research, and it can be adopted and improved for other domains, such as vaccine, medical devices.